Optimization of culture conditions of microalgae in an algal-bacterial system by response surface method - LUO Longzao; ZENG Fanjian; TIAN Guangming (浙江大学学报. 农业与生命科学版)
An algal-bacterial system was constructed to explore the effects of culture conditions on the growth of microalgae. On the basis of the results of single factor test, three factors including the agitating rate, the initial inoculation ratio of microalgae and bacteria, and the organic load of the wastewater were optimizated by using the response surface method. The results showed that the microalgal growth was significantly affected by airtight condition, agitation rate, initial inoculation ratio and organic load of the culture system, and the microalgae grew better in the open culture system. The optimum condition by the response surface optimization was as follows: agitating rate of 1 574.29 r/min, inoculation ratio 150∶1 of bacteria-alga and organic load (chemical oxygen demand, COD) of 3 676.02 mg/L. After seven days of culture under the optimimum condition, the biomass of microalgae was 5.68 g/L, which was in accordance with the theoretically predicted value (5.69 g/L). The above results can lay a scientific basis for improving the resource recovery efficiency from wastewater by algal-bacterial system.